Asymmetric supercapacitors based on transition metal oxides induced pseudocapacitance - Mak, Wai Fatt (2013)
Pseudocapacitor exhibiting higher capacitance and energy density than electrochemical double layer capacitor (EDLC) and delivering greater power density than batteries represent unique charge storage devices that bridge the gap of EDLC and rechargeable battery. In particular, Ru02 based material has received much attention in past decades. However, they are expensive due to their scarce resources. This study